2019
DOI: 10.3390/cancers11101413
|View full text |Cite
|
Sign up to set email alerts
|

Proton Beam Therapy Combined with Intra-Arterial Infusion Chemotherapy for Stage IV Adenoid Cystic Carcinoma of the Base of the Tongue

Abstract: Adenoid cystic carcinoma (ACC) is a very rare epithelial tumor of the salivary glands. Surgical resection is considered to be a standard therapy. However, the optimal treatment strategy for managing advanced cases has not yet been established. This study evaluated the efficacy and toxicity of proton beam therapy (PBT) combined with selective intra-arterial infusion chemotherapy (IAIC) using weekly cisplatin for locally advanced ACC of the base of the tongue. Between March 2009 and February 2018, 15 patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Fossum et al reported 1 of 11 (9.1%) patients with Common Terminology Criteria for Adverse Events grade 3 ORN in the right mandible following PRT with 60 GyRBE for right mandibular gingival cancer. Takayama et al reported 1 of 15 (6.6%) patients with grade 2 CTCAE ORN after PRT and intra-arterial infusion chemotherapy for adenoid cystic carcinoma of the base of the tongue. Thus, the ORN rate in our study (10.6%) is higher than the previously reported prevalence of 4% to 8% in the modern era …”
Section: Discussionmentioning
confidence: 99%
“…Fossum et al reported 1 of 11 (9.1%) patients with Common Terminology Criteria for Adverse Events grade 3 ORN in the right mandible following PRT with 60 GyRBE for right mandibular gingival cancer. Takayama et al reported 1 of 15 (6.6%) patients with grade 2 CTCAE ORN after PRT and intra-arterial infusion chemotherapy for adenoid cystic carcinoma of the base of the tongue. Thus, the ORN rate in our study (10.6%) is higher than the previously reported prevalence of 4% to 8% in the modern era …”
Section: Discussionmentioning
confidence: 99%
“…The included research spanned the years 2006 to 2022, with publications from different regions. Among the 14 included studies, 2 were from the USA, 20 , 21 3 from China, 22 24 4 from Japan, 25 28 4 from Germany, 29 32 and 1 from Switzerland. 33 …”
Section: Resultsmentioning
confidence: 99%
“…Many reports exist of AME cases successfully treated with BRAF kinase or inhibitors, yet this treatment option still faces may challenges mostly associated with toxicity and acquired resistance [ 48 ]. Moreover, AC is a malignant tumor that lacks a specific systemic therapy and is mostly managed by surgical resection with adjuvant radiotherapy or conventional chemotherapy if needed [ 49 ]. Recently, the use of a new group of drugs, recognized as epi-drugs, has emerged as a promising therapeutic option in target therapy aiming to restore deregulated epigenetic mechanisms.…”
Section: Discussionmentioning
confidence: 99%